THE CONCEPT OF POLITICAL PERSUASIONS AND ITS PHILOSOPHICAL CONTENT - Shernazarov Ravshan Avazovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, the concept of “Political persuasion” and its concrete structure expressing the views, thoughts and decisions of a person in the field of politics are conceptually analyzed. It is also revealed that this concept is important in the formation of forms and systems of political processes, plays an important role in the development of the state and society, and helps in the analysis of human experience, social issues and views